Loteprednol etabonate gel 0.5% for postoperative pain and inflammation after cataract surgery: results of a multicenter trial - Fong R (Dove Medical Press, 2012)
Raymond Fong,1 Martin Leitritz,2 Raphaele Siou-Mermet,3 Tara Erb41Manhattan Eye, Ear and Throat Hospital, Lenox Hill Hospital, New York, NY, USA; 2Department of Ophthalmology, University Eye Hospital Tübingen, University of Tübingen, Tübingen, Germany; 3Bausch and Lomb, Montpellier, France; 4Bausch and Lomb, Rochester, NY, USAPurpose: Loteprednol etabonate (LE) is approved by the US FDA in a suspension and ointment form (0.5%) for the treatment of postoperative ocular inflammation. This study examined the gel formulation of LE, an improved, nonsettling formulation with a lower preservative level and a more physiologic pH.Patients and methods: This multicenter, double-masked, parallel-group, vehicle-controlled study randomized patients aged ≥18 years with postoperative anterior chamber cell (ACC) ≥ grade 2 following uncomplicated cataract surgery to either LE gel or vehicle four times a day for 14 days. Primary efficacy end points included the proportion of patients with complete resolution of ACC and grade 0 (no) pain by postoperative day 8. Secondary efficacy end points included complete resolution and change from baseline in ACC and flare (individual and combined), and grade 0 pain at each visit. Safety end points included treatment-emergent adverse events, ocular symptoms, changes in intraocular pressure (IOP) and visual acuity, and biomicroscopy and funduscopy findings.Results: A total of 407 patients were randomized to treatment (n = 206, LE gel; n = 201, vehicle). At day 8, 31.1% (64) of LE-treated patients and 13.9% (28) of vehicle-treated patients had complete resolution of ACC (P < 0.001), and 75.7% (156) of LE-treated patients and 45.8% (92) of vehicle-treated patients had grade 0 pain (P < 0.001). Secondary efficacy end points also favored LE gel. Fewer patients treated with LE gel required rescue medication (10.7% versus 42.3%) prior to day 15, and fewer had an ocular adverse event (16.0% versus 28.9%, P = 0.002). No drug-related adverse effects were reported more than once in the LE group. Mean IOP decreased in both treatment groups; one patient in the LE group demonstrated a clinically significant increase (≥10 mm Hg) in IOP that was not considered drug-related. Visual acuity and funduscopy findings were similar between treatments.Conclusion: LE gel 0.5% was efficacious and safe in treating postoperative inflammation and pain in this clinical study.Keywords: cataract surgery, corticosteroids, gel, loteprednol etabonate, postoperative inflammation, postoperative pain